The benefits of studying abroad for one or two years (Journal of Parents and Teachers, 2026)
An increasingly common reality in the world of education is the opportunity to spend a term studying abroad. It is very important to be clear about what you are looking for and what you might find, so that the experience can have a positive impact. The author of the article suggests some objectives that might be set by those who decide to study abroad for a period, such as learning a language, discovering a new way of life, and developing one’s ability to adapt, be independent and make decisions. It can also help you get to know yourself better, cultivate an open mind, boost your self-esteem and improve your interpersonal skills.
Keywords: studying abroad; languages learning; settling in; independence; social skills